PEMBELAJARAN AQIDAH AKHLAK DENGAN PENDEKATAN KONTEKSTUAL UNTUK MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK SMK IBNU KHALDUN BALIKPAPAN - Sholihin (UNISAN JURNAL, 2024)
This investigation means to choose the learning of moral aqidah using a sensible system. The investigation procedure uses abstract assessment. Learning Aqidah Akhlak using a pertinent procedure might perhaps additionally foster learning achievement at SMK Ibnu Khaldun Balikpapan . By applying this technique, there are a couple of things that can be worried: 1) Extending Student Commitment: The setting focused approach grants students to be successfully drawn in with the instructive involvement in material on Islamic severe thoughts and everyday presence conditions. This can assemble students' benefit and motivation in learning in light of the fact that the learning material becomes significant and huge for them; 2) More significant Understanding: Students can fathom Islamic severe thoughts in greater significance since they can see how these thoughts partner with the reality of their lives. This helps students with acclimatizing Islamic severe characteristics better; 3) Improvement of Conclusive Thinking skills: Through legitimate learning, students are free to show Islamic severe thoughts in significant conditions that are ordinary to them